Police and Criminal Evidence Act 1984 (PACE) - Code C : Revised code of practice for the detention, treatment and questioning of persons by police officers.: Revised code of practice for the detention, treatment and questioning of persons by police officers. (November 2016) - Great Britain., Home Office,
No abstract available